Evil : an investigation - Morrow, Lance (New York : Basic Books, 2003)
"Drawing on examples both obscure and splashed across the front page, Morrow asks if, ultimately, we can understand evil - or if we even should. From Caligula to Columbine to his encounter with Milosevic, Morrow's stories are drawn from over thirty years of experience as a revered journalist and essayist. The result is a synthesis of a lifetime of observation that illuminates the chronically elusive, endlessly fascinating paradox that is evil."--BOOK JACKET.
1. The Globalization of Evil -- 2. Humor's Cousin -- 3. A Current Through the World -- 4. Why Do They Do It? -- 5. The Hermit's Tale -- 6. A Catastrophic Education -- 7. The Axis of Wrong -- 8. Sarajevo: Lex Talionis -- 9. The Rifleman's Dilemma -- 10. Jean Valjean at Wendy's -- 11. Visigoths in the Brain -- 12. The Axe in Space -- 13. What Have Children to Do with It? -- 14. The Triumph of Goneril and Regan -- 15. Tu Quoque -- 16. The Rattlesnake in the Mailbox -- 17. Permissible Evil -- 18. Taking Responsibility for the Regime -- 19. Office Malignities -- 20. The Consolations of Literature -- 21. Us and Them -- 22. The Face's Secrets -- 23. Club Med for Monsters -- 24. Sade, Cobain, and the Pleasures of Evil -- 25. Gourmets and Monkey Brains -- 26. The Limits of Silence -- 27. The Argument from Design -- 28. It Is Always a Story -- 29. The Lessons of Mein Kampf -- 30. What Nachtwey Sees -- 31. The Quest for Purity -- 32. The Foxes Lose Heart -- 33. Czerniakow's Choice -- 34. Hope.
Includes index.
Keywords: Good and evil